Budget Allocation Strategy of Bogor City Health Department in the Covid-19 Era - Revinadewi, Tia; Hakim, Dedi Budiman; Falatehan, A Faroby (JURNAL MANAJEMEN AGRIBISNIS; Vol 9 No 2 (2021): OKTOBER 2021DO - 10.24843/JMA.2021.v09.i02.p11, 2021)
The authority of the local government in the Replacement Government Law No. 1 of 2020 is that the Local Government is given the authority to prioritise the use of budget allocations for certain activities (refocusing). One of the areas in Indonesia affected by Covid-19 is Bogor City, Bogor City is one of the cities close to the capital and becomes one of the cities with transmission through imported cases originating from outside the region.  The proportion of bogor health budget in 2020 is prioritized for Covid-19 prevention. The purpose of this study explains the state of the budget of the Bogor City Health Office during Covid-19 and explains the use of the Covid-19 budget in accordance with the objectives and formulates a budget allocation strategy based on the existing budget. The type of dtaa used in this study is primary data obtained through in-depth interviews with virtue takers related to using analytical hierarchy process (AHP) questionnaires and secondary data obtained from the Health Office, Regional Planning and Development Agency and Bogor City Asset Finance Agency.